Management of Proceeds of Crime in International and Comparative Law (Kriminalističke teme, 2018)
Reason(s) for writing and research problem(s): Confiscation of the proceeds of crime is a long-term existing measure in national legislations, reflecting a principle that no one should profit from crime. Although recently progress has been made, there are difficulties in its implementation. In order to have effective criminal confiscation, it is quintessential to develop a comprehensive legal framework regulating all important procedural aspects, from identification, provisional and permanent deprivation of crime assets, to management of proceeds of crime. Part of the problem rests in inadequate and fragmented legal framework governing management of proceeds of crime. This paper reviews relevant matters associated with the management of confiscated assets in international and comparative law.Aims of the paper (scientific and/or social): Review of provisions stipulated in relevant international conventions and other documents in the field of management of proceeds of crime can provide insight into standards, and identify similarities and dissimilarities in reviewed legal systems as well.Methodology/Design: Analyses in this paper utilize comparative and hermeneutical legal approach in description of stipulations in selected international conventions and national legislations. International conventions and other legal documents are selected based on their importance and relevance for the area of management of criminal assets. National legislations are selected based on legal tradition, experience in criminal assets confiscation, and similarities with the Bosnian-Herzegovinian legal mechanisms.Research/paper limitations: The volume of the paper limits the quantity of legal documents and approaches that could be analysed in detail. Conclusions about the approaches are limited to publicly available legal material. It is rather likely that details in the matters of management of criminal assets regulated by books of rules or similar supporting acts, usually not publicly available.Results/Findings: International conventions usually do not impose any mandatory requirements related to management of confiscated proceeds, but state parties should enable a comprehensive system on identification, tracing, freezing or seizure of any property for the purpose of confiscation. Approaches taken in reviewed national jurisdictions enable freezing and seizure as typical measures of provisional securing the proceeds from crime, and sale as most common form of disposal.General conclusion: Appropriate and relevant legal framework is an important factor in both judicial order and enforcement of criminal confiscation, which includes harmonisation of regulations in criminal, civil and other branches of law. For the purpose of strengthening public`s confidence in justice system, it is important to demonstrate effectiveness of confiscation mechanisms, particularly by re-use of property by individuals and communities from which they were illegally taken.Research/paper validity: An analysis of legal framework disciplining seizure and disposal of the proceeds of crime is a valuable effort in domestic legal theory. The resulting analysis and review could serve as reference point for improvement of national legal framework.